Evaluation efficiency of salinity tolerant Trichoderma harzianum for alleviation of salinity stress in date palm (Phoenix dactylifera L.) - Jassim, Naji S; Alhamd, Abdulrahman D; Ati, Muntha Abd-Z (Journal of Degraded and Mining Lands Management, 2025)
This study aimed to determine the benefit of a bioagent (Trichoderma hazianum) to lessen the adverse effects of NaCl stress on date palm offshoots (Phoenix dactylifera L.) Varying concentrations of sodium chloride (NaCl) (0, 5, 10, 15, 20, and 25 dS m-1) were used to observe the effect on photosynthetic pigments, antioxidant enzymes, total proline, total phenolics, and hydrogen peroxide in date palm offshoots in the presence and absent of the bioagent T. harzainum. Results of the study showed that enhancing the NaCl concentration from 10-20 dS m-1 did not affect the mycelial growth colony of the T. harzianum in the potato dextrose agar (PDA) medium. The results indicated a significant increase in photosynthetic pigments (chlorophyll and carotenoid), levels of peroxidase and catalase enzymes, total proline, and total phenolic content in the date palm offshoots with the application of T. harzainum. A higher concentration of NaCl leads to a higher level of hydrogen peroxidation. Additionally, salt stimulated the production of antioxidant enzymes such as catalase and peroxidase. The study has indicated a significant reduction in salt stress's negative physiological and biochemical effects on date palm offshoots after applying the bioagent T. harzianum. This study showed that Trichoderma, with its ability to promote plant growth, may be employed to increase the growth of date palm offshoots developing under NaCl stress conditions.